Security analysis of mobile banking - Tok, Jonus Jun Ming (2018)
This report provides a comprehensive theoretical study on security analysis of mobile banking. As mobile banking gets more and more efficient and convenient in recent years, security is as important as ever. It will be disastrous if sensitive information is obtained by attackers who wants to make use of such information for their own benefit. Currently, there are several security protocols existing in the real world, such as Hypertext Transfer Protocol Secure (HTTPS), two factor authentications (2FA), Rivest-Shamir-Adleman (RSA), Advanced Encryption standard (AES), Message Authentication Code (MAC) and Secure remote password protocol (SRP). This paper aims to study and research on the existing protocols and understand their vulnerability to security attacks. This paper also aims to research and study the algorithms behind DBS Paylah! security protocol (OAUTH) and attempts to apply SRP concepts on an imaginary bank to demonstrate how SRP can overcome the theoretical shortcomings of Oauth.